Should franchise restaurant companies own so much real estate? - Abraham Park (Global Business & Finance Review (GBFR), 2016)
This paper examines the performance effects of corporate real estate (CRE) ownership for franchise restaurant companies. Although several studies have investigated the performance effects of franchise firms (Leleux et al., 2003; Aliouche and Schlentrich, 2009; Hsu and Jang, 2009; Madanoglu et al., 2011; Aliouche, Kaen and Schlentrich, 2012), no previous study has focused on the performance effects of corporate real estate ownership on franchise restaurant companies. McDonalds was one of the earliest of companies that have extensively used CRE as a source of strategic advantage and as a way to reduce the agency costs associated with franchising. As retail companies seek to assemble valuable CRE portfolios that can generate sustainable competitive advantages, inferior or inefficient locations can significantly undermine their long-term financial performance. Furthermore, the existing franchise research has largely ignored the danger of over-exposure of real estate risk, as highlighted by the most recent global financial crisis. For these reasons and more, CRE ownership has the potential to significantly impact the performance of franchise restaurant companies and this paper seeks to fill this gap in franchise literature. By testing the effect of CRE ownership level on abnormal returns (Jensen's alpha) and systematic risk (beta) of public franchise restaurant companies, we find that the CRE level has a significantly negative impact on the abnormal returns and significantly positive impact on the systematic risk of franchise restaurant firms, as well as restaurants in general. Considering that non-franchise companies have higher average levels of CRE ownership, this study provides a partial explanation as to the outperformance of franchise restaurant companies compared to non-franchise restaurant companies.
Keywords: 650; Franchises; Franchise Performance; Corporate Real Estate